KAMPUNG HIJAU PADA KAMPUNG KOTA (STUDI KASUS: KAMPUNG TANJUNG GEDONG RT.05/ RW.08, JAKARTA BARAT) - Solikhah, Nafiah; Fatimah, Titin (Jurnal Bakti Masyarakat Indonesia, 2020)
The village is an integral part of cities in Indonesia since its inception. Each village is unique because it represents historical uniqueness, diverse physical patterns, complex and dynamic social systems. Jakarta City as the largest city in Indonesia has its own challenges in managing the Urban Villages. One of the urban villages in Jakarta is Tanjung Gedong Village, located in RT.05 / RW.08 Tomang Village, Grogol Petamburan District. The selection of RT.05 / RW.08 as a PKM activity partner was because the location of the target partner was around the UNTAR campus, so the PKM activity became a tangible manifestation of UNTAR's contribution to the surrounding environment. The Proposing Team has also conducted PKM activities at the Partner's location, so it is hoped that the proposed program will be sustainable. Tanjung Gedong Village RT.05 / RW.08 Tomang Village has an area of 1.3 hectares with a population of 300 people (60 households). Problems owned by Partners to create a healthy and comfortable environment for residents: First, spatial planning is not optimal and flexible to accommodate a variety of social activities from the community. Secondly, the partners currently lack green open space. The proposed solution is the Proposed Green Village Structuring Concept by involving active participation from Partners (RW-RT leadership, Residents) using 3 approaches, namely: Green Planning and Design, Green Open Space and Green community. The proposed Green Village concept is expected to overcome the problems faced by partners so that a healthy and comfortable residential environment for residents is achieved ABSTRAK: Kampung merupakan bagian integral kota-kota di Indonesia sejak awal pembentukannya. Setiap kampung memiliki keunikan karena merepresentasikan kekhasan sejarah, pola fisik yang beragam, sistem sosial yang kompleks dan dinamis. Kota Jakarta sebagai kota terbesar di Indonesia memiliki tantangan tersendiri dalam mengelola Kampung Kotanya. Salah satu kampung kota di Jakarta adalah Kampung Tanjung Gedong yang terletak di RT.05/RW.08 Kelurahan Tomang, Kecamatan Grogol Petamburan. Pemilihan RT.05/RW.08 sebagai Mitra kegiatan PKM karena lokasi mitra sasaran berada di sekitar kampus 1 UNTAR, sehingga kegiatan PKM ini menjadi salah satu wujud nyata kontribusi UNTAR terhadap lingkungan sekitar. Tim Pengusul juga telah melakukan kegiatan PKM di lokasi Mitra, sehingga diharapkan program yang diusulkan akan berkesinambungan. Kampung Tanjung Gedong RT.05/RW.08 Kelurahan Tomang memiliki luasan 1,3 Ha dengan jumlah penduduk 300 orang (60 KK). Permasalahan yang dimiliki oleh Mitra untuk menciptakan lingkungan yang sehat dan nyaman untuk warga: Pertama, tata ruang belum optimal dan fleksibel untuk mewadahi beragam aktivitas sosial dari masyarakat. Kedua, saat ini mitra masih kekurangan ruang terbuka hijau. Solusi yang diusulkan adalah Usulan Konsep Penataan Kampung Hijau dengan melibatkan partisipasi aktif dari Mitra (pemangku pimpinan RW-RT, Warga) menggunakan 3 pendekatan, yaitu: Green Planning and Design, Green Open Space dan Green community. Usulan konsep Kampung Hijau diharapkan dapat mengatasi permasalahan yang dihadapi oleh mitra sehingga tercapai sebuah lingkungan hunian yang sehat dan nyaman untuk warga.